Enhanced oral bioavailability of cannabidiol by flexible zein nanoparticles: in vitro and pharmacokinetic studies - Nie, YingLan; Kong, Yan; Peng, Juan; Sun, Jian; Fan, Bin (Frontiers in Nutrition, 2024)
Cannabidiol (CBD) has a variety of pharmacological effects including antiepileptic, antispasmodic, anxiolytic and anti-inflammatory among other pharmacological effects.However, since CBD is a terpene-phenolic compound, its clinical application is limited by its poor water solubility, low stability, and low bioavailability. In this study, we used several strategies to address the above problems. Hydrochloric acid was used to modify zein to improve the molecular flexibility. Flexible zein nanoparticles (FZP-CBD) loaded with CBD was prepared to improve the stability and bioavailability of CBD. The parameters were evaluated in terms of morphology, particle size (PS), polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE%), loading capacity (LC%), and storage stability. Simulated gastrointestinal fluid release experiment and bioavailability assay were applied in the evaluation. The simulated gastrointestinal fluid experiment showed that the release rates of FZP-CBD and natural zein nanoparticles (NZP-CBD) loaded with CBD were 3.57% and 89.88%, respectively, after digestion with gastric fluid for 2 h, 92.12% and 92.56%, respectively, after intestinal fluid digestion for 2 h. Compared with NZP-CBD, the Cmax of FZP-CBD at 3 different doses of CBD was increased by 1.7, 1.3 and 1.5 times respectively, and AUC0-t was increased by 1.4, 1.1 and 1.7 times respectively, bioavailability (F) was increased by 135.9%, 114.9%, 169.6% respectively. The experimental results showed that FZP-CBD could protect most of the CBD from being released in the stomach, and then control its release in the intestines, promote the absorption of CBD in the small intestine, and increase the bioavailability of CBD. Therefore, FZP-CBD could improve the utilization value of CBD and provide a new idea for the application of CBD in medicine and pharmacy.